Visually Impaired People’s Demand for Supermarket Public Environment and ptimal Design from the Perspective of Perceptual Behavior - Li, Shizhe; You, Zhenwei (Art & Design Research, 2022)
Through the sequential action notation method, the visually impaired people’s perception needs and behavioral characteristics of the supermarket environment are deeply explored, and the optimization of the barrier-free design of the supermarket public environment is provided. Use the sequential action notation method to grasp the personal experience pre-demands of the visually impaired individuals for public spaces, and by recording the behaviors of the visually impaired people in the shopping process of the supermarket, combined with semi-structured interviews, to conduct an in-depth analysis of their needs in the supermarket environment. Dig and analyze to find the design entry point. Visually impaired people appreciate coherent, predictable layouts and horizontal and vertical movements. The three major obstacles in supermarket shopping for visually impaired people are the obstacle of walking alone in the supermarket, the obstacle of obtaining information on the distribution of the supermarket area, and the obstacle of obtaining detailed information of goods. This design research uses multi-channel sensory and RFID technology to provide safe and autonomous purchasing services for visually impaired people.